2008
DOI: 10.3168/jds.2007-0610
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Concentrations of Lysine, Methionine, and Threonine in Milk Replacers for Calves Less than Five Weeks of Age

Abstract: The AA requirements of herd-replacement calves less than 5 wk old and fed milk replacers are not clearly defined and have been estimated in a limited number of studies using milk-fed calves ranging from 5 to 20 wk of age. The objective of these 4 studies was to investigate the effect of supplementing milk replacers containing 24 to 28% crude protein (CP; from milk sources) and 17% fat with Lys, Met, and Thr to estimate the optimum requirements for calves less than 5 wk of age. Holstein bull calves (initially 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 15 publications
2
76
3
Order By: Relevance
“…At observed CP, Lys, and Met concentrations of about 29, 2.59, and 0.57% DM in the SMWP diet, the respective average nutrient intakes must have been approximately 275, 25, and 5.41 g/d, with a concomitant observed ADG, Lys efficiency, and Met efficiency of around 0.89 kg/d, 38 g of BW gain/g of Lys, and 165 g of BW gain/g of Met (data not shown for first 4 wk). Hill et al (2008b) reported maximal ADG of 0.46 kg/d with CP, Lys, and Met intakes of 204, 17, and 5.3 g/d, respectively, for calves fed about 0.65 kg of DM/d of a 26% CP/17 fat milk replacer. Based on those findings, Hill et al (2008b) established a requirement for calves less than 5 wk old averaging 48 kg of BW and fed 0.65 kg of DM/d to be met with 17 g/d of Lys and 0.31 Met:Lys.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…At observed CP, Lys, and Met concentrations of about 29, 2.59, and 0.57% DM in the SMWP diet, the respective average nutrient intakes must have been approximately 275, 25, and 5.41 g/d, with a concomitant observed ADG, Lys efficiency, and Met efficiency of around 0.89 kg/d, 38 g of BW gain/g of Lys, and 165 g of BW gain/g of Met (data not shown for first 4 wk). Hill et al (2008b) reported maximal ADG of 0.46 kg/d with CP, Lys, and Met intakes of 204, 17, and 5.3 g/d, respectively, for calves fed about 0.65 kg of DM/d of a 26% CP/17 fat milk replacer. Based on those findings, Hill et al (2008b) established a requirement for calves less than 5 wk old averaging 48 kg of BW and fed 0.65 kg of DM/d to be met with 17 g/d of Lys and 0.31 Met:Lys.…”
Section: Resultsmentioning
confidence: 96%
“…Hill et al (2008b) reported maximal ADG of 0.46 kg/d with CP, Lys, and Met intakes of 204, 17, and 5.3 g/d, respectively, for calves fed about 0.65 kg of DM/d of a 26% CP/17 fat milk replacer. Based on those findings, Hill et al (2008b) established a requirement for calves less than 5 wk old averaging 48 kg of BW and fed 0.65 kg of DM/d to be met with 17 g/d of Lys and 0.31 Met:Lys. From their data it is possible to calculate their Lys and Met efficiency must have been around 27 and 87 g of BW gain per g of Lys and Met, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In vitro studies have shown lysine has a replication-inhibiting capability of the herpes virus (Maggs et al, 2000). Since IBR is the result of a herpes virus infection, there may be an altered response to the common IBR vaccination when lysine is supplemented at concentrations exceeding requirements of 17g/d determined by Hill et al (2007). The objective of this study was to investigate the effects of a lysine supplementation on a modified-live viral respiratory vaccine.…”
Section: Introductionmentioning
confidence: 99%